Impaired orienting function detected through eye movements in patients with temporal lobe epilepsy - Wen, Shirui; Zhang, Huangyemin; Huang, Kailing; Wei, Xiaojie; Yang, Ke; Wang, Quan; Feng, Li (Frontiers in Neuroscience, 2023)
Objective: Patients with temporal lobe epilepsy (TLE) often exhibit attention function impairment. The orienting network is the sub-system of the attention network that has not been fully studied. In this study, we used eye-tracking technology with the attention network test (ANT)-based task to assess the orienting function of TLE patients, aiming to characterize their eye movement patterns. Methods: 37 TLE patients and 29 healthy controls (HCs) completed the ANT task based on eye-tracking technology. Orienting function damage was mainly assessed by ANT-orienting-effect. The eye movement metrics were compared between groups, such as mean first goal-directed saccade latency (MGSL), total saccades, and saccade amplitudes. Results: The TLE patients had significantly lower ANT-orienting-effect (HC: 54.05 ± 34.05, TLE: 32.29±39.54) and lower eye-tracking-orienting-effect (HC: 116.98 ± 56.59, TLE: 86.72±59.10) than that of the HCs. The larger orienting effects indicate that orienting responses are faster when receiving a spatial cue compared to a center cue. In the spatial cue condition, compared to HCs, the TLE group showed longer first goal-directed saccade latency (